Istikhdāmu Qāmūsi al Arabiyyati al ‘Āmati fī Tarjamati al Kutubi al ‘Arabiyyati ‘inda Ṭullabi al Jāmi’ati al Ḥukūmiyyati Jāmbi - Patela, Rekson; Fahri, Ismail (Jurusan Bahasa dan Sastra Arab Fakultas Adab dan Humaniora UIN Sulthan Thaha Saifuddin Jambi, 2020)
In the Arabic language department in Jambi, there is an Arabic book translation activity that is done using Arabic dictionaries to know the meaning and Improve The Ability and Advice in using the dictionary. The activity of learning the procedure of opening a dictionary, searching for specific vocabulary and sentences by using dictionaries in the translation process. The targets/respondents of this study were students majoring in Arabic Language and Satra who were in Jambi college in The Class/Semester III and V. Data collection techniques by disseminating questionnaires, Observations, And Interviews. Data Analysis is done qualitatively. The results of this study found the difficulty and ease of Students in using Arabic dictionaries and Providing Improvement, knowledge, and advice to students on how to use dictionaries as translation tools for Arabic books. Through this research, the activity is intended as an Evaluation of The Proficiency of Arabic Language Students in Using dictionaries as translation tools. Thus, the result of the study is to know the establishment of students in using dictionaries as a translation tool for Arabic books